2022
DOI: 10.3390/ijms23147736
|View full text |Cite
|
Sign up to set email alerts
|

Trypsin-like Inhibitor Domain (TIL)-Harboring Protein Is Essential for Aedes aegypti Reproduction

Abstract: Cysteine-rich trypsin inhibitor-like domain (TIL)-harboring proteins are broadly distributed in nature but remain understudied in vector mosquitoes. Here we have explored the biology of a TIL domain-containing protein of the arbovirus vector Aedes aegypti, cysteine-rich venom protein 379 (CRVP379). CRVP379 was previously shown to be essential for dengue virus infection in Ae. aegypti mosquitoes. Gene expression analysis showed CRVP379 to be highly expressed in pupal stages, male testes, and female ovaries. CRV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
0
0
0
Order By: Relevance
“…Based on a conserved-domain search, we found that the TIL domain was also present in serpins of nine other lepidopteran insects (A. transitella, D. plexippus, H. armigera, H. melpomene, M. cinxia, P. rapae, P. xuthus, S. litura, and T. ni) that were used for comparative genomics analysis. Previous studies have reported that the TIL domain-containing proteins are mainly involved in regulating the host immune response by inhibiting the protease cascade reaction [66][67][68] and by participating in the regulation of mosquito reproduction [69]; thus, we inferred that the function of CpSPN25 might be an immune inhibitor. As with the PRK13335 (annotated as superantigen-like protein 3 in the NCBI CDD) and PRK08581 (annotated as amidase domain-containing protein) superfamily domains, the former was only found in CpSPN26, while the latter was also detected in BmSPN27.…”
Section: Discussionmentioning
confidence: 84%
“…Based on a conserved-domain search, we found that the TIL domain was also present in serpins of nine other lepidopteran insects (A. transitella, D. plexippus, H. armigera, H. melpomene, M. cinxia, P. rapae, P. xuthus, S. litura, and T. ni) that were used for comparative genomics analysis. Previous studies have reported that the TIL domain-containing proteins are mainly involved in regulating the host immune response by inhibiting the protease cascade reaction [66][67][68] and by participating in the regulation of mosquito reproduction [69]; thus, we inferred that the function of CpSPN25 might be an immune inhibitor. As with the PRK13335 (annotated as superantigen-like protein 3 in the NCBI CDD) and PRK08581 (annotated as amidase domain-containing protein) superfamily domains, the former was only found in CpSPN26, while the latter was also detected in BmSPN27.…”
Section: Discussionmentioning
confidence: 84%